2023
DOI: 10.3390/ijms24032307
|View full text |Cite
|
Sign up to set email alerts
|

Aqua/Mechanochemical Mediated Synthesis of Novel Spiro [Indole–Pyrrolidine] Derivatives

Abstract: Spirocyclic scaffolds are found in many pharmacologically active natural and synthetic compounds. From time to time, efforts have been made to develop new or better processes for the synthesis of spirocyclic compounds. Spiro [Indole–pyrrolidine] Derivatives are readily synthesized in high to excellent yields by the Michael condensation of 3-dicyanomethylene-2H-indol-2-ones (produced via the Knoevenagel condensation of indole-2,3-dione with malononitrile) with isothiocyanate derivatives under aqueous and mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Thus, we found that liquid‐assisted mechanochemical activation was efficient and valuable in our work with respect to yields and experimental simplicity [28] . Other mechanochemically activated multicomponent reactions (MCRs) have afforded various novel spiro‐[ indole‐pyrrolidine], thiophene, and 4H‐pyran derivatives [29,30,31] …”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, we found that liquid‐assisted mechanochemical activation was efficient and valuable in our work with respect to yields and experimental simplicity [28] . Other mechanochemically activated multicomponent reactions (MCRs) have afforded various novel spiro‐[ indole‐pyrrolidine], thiophene, and 4H‐pyran derivatives [29,30,31] …”
Section: Introductionmentioning
confidence: 85%
“… [28] Other mechanochemically activated multicomponent reactions (MCRs) have afforded various novel spiro‐[ indole‐pyrrolidine], thiophene, and 4H‐pyran derivatives. [ 29 , 30 , 31 ]…”
Section: Introductionmentioning
confidence: 99%
“…Examples of mechanochemical reactions include ball milling, sonication, and grinding of solid reactants to produce new compounds with unique properties. Such reactions have been reported for the synthesis of various inorganic [8] or organic molecules [9,10] or supramolecular structures [11,12], such as co-crystals, polymorphs, metal-organic frameworks, covalent-organic frameworks, and coordination polymers, with a plethora of scientific and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Spiroheterocyclic motifs are present in a number of approved drugs and natural compounds [ 1 , 2 , 3 , 4 ] ( Figure 1 ). Such an interest in spirocyclic structures echoed in the field of synthetic organic chemistry, giving rise to a number of elegant preparative approaches to compounds of this type [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%